Effects of a 10-week resistance exercise program on soccer kick biomechanics and muscle strength - Manolopoulos, E.; Katis, A.; Manolopoulos, K.; Kalapotharakos, V.; Kellis, E. (The Journal of Strength and Conditioning Research, 2013)
The purpose of the study was to examine the effects of a resistance exercise program on soccer kick biomechanics. Twenty male amateur soccer players were divided in the experimental group (EG) and the control group (CG), each consisting of 10 players. The EG followed a 10-week resistance exercise program mainly for the lower limb muscles. Maximal instep kick kinematics, electromyography, and ground reaction forces (GRFs) as well as maximum isometric leg strength were recorded before and after training. A 2-way analysis of variance showed significantly higher ball speed values only for the EG (26.14 ± 1.17 m/s vs. 27.59 ± 1.49 m/s before and after training, respectively), whereas no significant differences were observed for the CG. The EG showed a decline in joint angular velocities and an increase in biceps femoris electromyography of the swinging leg during the backswing phase followed by a significant increase in segmental and joint velocities and muscle activation of the same leg during the forward swing phase (p < 0.05). The EG also showed significantly higher vertical GRFs and rectus femoris and gastrocnemius activation of the support leg (p < 0.05). Similarly, maximum and explosive isometric force significantly increased after training only for the EG (p < 0.05). These results suggest that increases in soccer kicking performance after a 10-week resistance training program were accompanied by increases in maximum strength and an altered soccer kick movement pattern, characterized by a more explosive backward-forward swinging movement and higher muscle activation during the final kicking phase.